Epistatic Analysis of the Contribution of Rabs and Kifs to CATCHR Family Dependent Golgi Organization - Liu, Shijie; Majeed, Waqar; Grigaitis, Pranas; Betts, Matthew J.; Climer, Leslie K.; Starkuviene, Vytaute; Storrie, Brian (Frontiers in Cell and Developmental Biology, 2019)
Multisubunit members of the CATCHR family: COG and NRZ complexes, mediate intra-Golgi and Golgi to ER vesicle tethering, respectively. We systematically addressed the genetic and functional interrelationships between Rabs, Kifs, and the retrograde CATCHR family proteins: COG3 and ZW10, which are necessary to maintain the organization of the Golgi complex. We scored the ability of siRNAs targeting 19 Golgi-associated Rab proteins and all 44 human Kifs, microtubule-dependent motor proteins, to suppress CATCHR-dependent Golgi fragmentation in an epistatic fluorescent microscopy-based assay. We found that co-depletion of Rab6A, Rab6A’, Rab27A, Rab39A and two minus-end Kifs, namely KIFC3 and KIF25, suppressed both COG3- and ZW10-depletion-induced Golgi fragmentation. ZW10-dependent Golgi fragmentation was suppressed selectively by a separate set of Rabs: Rab11A, Rab33B and the little characterized Rab29. 10 Kifs were identified as hits in ZW10-depletion-induced Golgi fragmentation, and, in contrast to the double suppressive Kifs, these were predominantly plus-end motors. No Rabs or Kifs selectively suppressed COG3-depletion-induced Golgi fragmentation. Protein-protein interaction network analysis indicated putative direct and indirect links between suppressive Rabs and tether function. Validation of the suppressive hits by EM confirmed a restored organization of the Golgi cisternal stack. Based on these outcomes, we propose a three-way competitive model of Golgi organization in which Rabs, Kifs and tethers modulate sequentially the balance between Golgi-derived vesicle formation, consumption, and off-Golgi transport.